Factors Associated with Mortality after Nissen Fundoplication in Children - Baerg, Joanne; Thorpe, Donna; Gasior, Alessandra; Vannix, Rosemary; Tagge, Edward; Peter, Shawn St. (European Journal of Pediatric Surgery, 2015)
Purpose The purpose of this article was to identify factors associated with mortality after Nissen fundoplication in children.Methods After Institutional Review Board approval, children younger than 18 years, from two children's hospitals, with Nissen fundoplication performed between January 1994 and December 2010, were retrospectively reviewed. Inclusion required complete data and follow-up to October 2011. Survivors and nonsurvivors were compared, using t-tests for continuous and chi-square tests for categorical variables, to identify factors associated with mortality. Patient factors present before the first fundoplication were analyzed. Surgical factors were surgical complications, gastrostomy placement, operative technique, and redos. Logistic regression evaluated for independence of variables.Results A total of 823 children were identified, 412 were included and 63 died (15.3%). The median follow-up time for the cohort was 3.7 years (mean, 4.5 ± 3.2 years). For nonsurvivors, the median time to death after fundoplication was 6.0 months (mean, 13.2 ± 18.0 months). Significant factors after univariate analysis were surgical complications (p = 0.001), female gender (p = 0.001), neurological impairment (p = 0.010), and fundoplication performed before the age of 18 months (p = 0.035). Independent predictors were surgical complications, odds ratio (OR), 3.30 (95% confidence interval [CI], 1.31–8.29), neurological impairment, OR, 2.58 (95% CI, 1.38–4.83), fundoplication before the age of 18 months, OR, 2.46 (95% CI, 1.23–4.94), and female gender, OR, 2.25 (95% CI, 1.26–4.00).Conclusion After Nissen fundoplication in children, surgical complications, neurological impairment, fundoplication performed before the age of 18 months, and female gender are associated with mortality. The median time to death for nonsurvivors was 6 months.
Keywords: fundoplication; children; mortality; surgical complications